Stopped at Stalingrad : the Luftwaffe and Hitler's defeat in the East, 1942 - 1943 - Hayward, Joel 1964- (Modern war studies, 1998)
Most accounts of the Battle of Stalingrad have focused on the dismal fate of the German Army. Joel Hayward now chronicles Luftwaffe operations during that campaign, focusing on Hitler's use of the air force as a tactical rather than strategic weapon in close support of ground forces